Control of fruit softening and Ascorbic acid accumulation by manipulation of SlIMP3 in tomato. Issue 6 (15th March 2022) - Zheng, Xianzhe; Yuan, Yujin; Huang, Baowen; Hu, Xiaowei; Tang, Yuwei; Xu, Xin; Wu, Mengbo; Gong, Zehao; Luo, Yingqing; Gong, Min; Gao, Xueli; Wu, Guanle; et al.
Summary: Postharvest deterioration is among the major challenges for the fruit industry. Regulation of the fruit softening rate is an effective strategy for extending shelf‐life and reducing the economic losses due postharvest deterioration. The tomato myoinositol monophosphatase 3 gene SlIMP3, which showed highest expression level in fruit, was expressed and purified. SlIMP3 demonstrated high affinity with the L‐Gal 1‐P and D‐Ins 3‐P, and acted as a bifunctional enzyme in the biosynthesis of AsA and myoinositol. Overexpression of SlIMP3 not only improved AsA and myoinositol content, but also increased cell wall thickness, improved fruit firmness, delayed fruit softening, decreased water loss, and extended shelf‐life. Overexpression of SlIMP3 also increased uronic acid, rhamnose, xylose, mannose, and galactose content in cell wall of fruit. Treating fruit with myoinositol obtained similar fruit phenotypes of SlIMP3‐ overexpressed fruit, with increased cell wall thickness and delayed fruit softening. Meanwhile, overexpression of SlIMP3 conferred tomato fruit tolerance to Botrytis cinerea . The function of SlIMP3 in cell wall biogenesis and fruit softening were also verified using another tomato species, Ailsa Craig (AC). Overexpression of SlDHAR in fruit increased AsA content, but did not affect the cell wall thickness or fruit firmness and softening. The results support a critical role for SlIMP3 in AsA biosynthesis and cell wall biogenesis, and provide a new method of delaying tomato fruit softening, and insight into the link between AsA and cell wall metabolism.